Orientasi Proses Karir Organisasional dan Keadilan Prosedural: Peran Keberagaman Individual - Budiadi, Nang Among (Jurnal Bisnis dan Kewirausahaan, 2019)
The advance of organizational justice construct along with its dimensions has potential implications in explaining many justice phenomena, including organizational career process orientation. Diversity of individuals in organization, especially between knowledge workers and non-knowledge workers will imply in different career need as well as their perceptions of organizational justice. The purpose of this research is to give perspective in the relationship between organizational career process and organizational justice. Organizational justice is explained by using organizational perspectives both externally and internally in four types of boundaryless careers (i.e., internal psychological, internal enacted, external psychological, and external enacted), and by considering individual characteristics (i.e., knowledge worker and nonknowledge worker). Two hipotesis were offered and tested using moderated regression analysis (MRA). Organization using organizational career process focusing on externalboundaries will be judged to be procedurally fair by knowledge workers. Organization using organizational career process focusing on internal boundaries will be judged to be procedurally fair by non-knowledge workers.